Clustered Charge-to-Alanine Mutagenesis of Human Respiratory Syncytial Virus L Polymerase Generates Temperature-Sensitive Viruses - Tang, Roderick S.; Nguyen, Nick; Zhou, Helen; Jin, Hong (Virology (New York, N.Y.), 2002)
Clustered charge-to-alanine mutagenesis was performed on the large (L) polymerase protein of human respiratory syncytial virus to identify charged residues in the L protein that are important for viral RNA synthesis and to generate temperature-sensitive viruses. Clusters of three, four, and five charged residues throughout the entire L protein were substituted with alanines. A minigenome replicon assay was used to determine the functions of the mutant L proteins and to identify mutations that caused temperature sensitivity by comparing the level of reporter gene expression at 39 and 33°C. Charge-to-alanine mutations were introduced into an antigenomic cDNA derived from RSV A2 strain to recover infectious viruses. Of the 27 charge-to-alanine mutations, 17 recombinant viruses (63%) were obtained. Seven mutants (41%) exhibited small plaque morphologies and/or temperature-sensitive growth in tissue culture. To generate mutant viruses with more temperature-sensitive and attenuated phenotypes, several clusters of charge-to-alanine substitutions were combined. Five combination mutants were recovered that exhibited shut-off temperatures ranging from 36 to 39°C in tissue culture and restricted replication in the respiratory tracts of cotton rats.